2018
DOI: 10.1007/s11606-018-4555-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Healthcare Access and Long-Term Survival After an Acute Coronary Syndrome

Abstract: Absence of an established usual source of care and inconsistent transportation availability were associated with a higher risk for dying after an ACS. Patients with these barriers to follow-up care may benefit from more intensive follow-up and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…People with unmet medical needs due to cost or without a usual source of care experience higher health costs and worse health outcomes, [37][38][39][40][41][42] and our findings indicate that these barriers are disproportionately more prevalent among racial and ethnic minorities.…”
Section: Discussionmentioning
confidence: 63%
“…People with unmet medical needs due to cost or without a usual source of care experience higher health costs and worse health outcomes, [37][38][39][40][41][42] and our findings indicate that these barriers are disproportionately more prevalent among racial and ethnic minorities.…”
Section: Discussionmentioning
confidence: 63%
“…The authors found that patients who reported difficulty accessing healthcare due to transportation issues the year prior to MI had increased mortality at 2 -years post-MI. However, there were only 239 patients who reported transportation to be an issue with accessing medical care and the increased mortality among these patients appears to be due entirely to the 44 patients who reported having all three of the healthcare access barriers present: transportation barriers, financial barriers, and lack of usual source of medical care [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found that nearly 40% of the sample would need to drive for >1 hour to access PrEP. Studies have shown that transportation barriers have a significant impact on health outcomes, particularly among disadvantaged individuals [32,33]. Regarding HIV care and treatment, travel time has been found to be a barrier to retention in care [34,35].…”
Section: Discussionmentioning
confidence: 99%